The relationship of autonomic imbalance, heart rate variability and cardiovascular disease risk factors - Thayer, Julian F.; Yamamoto, Shelby; Brosschot, Johannes Franciscus (International journal of cardiology, 2010)
Cardiovascular disease (CVD) is the leading cause of death and disability worldwide. The understanding of the risk factors for CVD may yield important insights into the prevention, etiology, course, and treatment of this major public health concern. Autonomic imbalance, characterized by a hyperactive sympathetic system and a hypoactive parasympathetic system, is associated with various pathological conditions. Over time, excessive energy demands on the system can lead to premature aging and diseases. Therefore, autonomic imbalance may be a final common pathway to increased morbidity and mortality from a host of conditions and diseases, including cardiovascular disease. Heart rate variability (HRV) may be used to assess autonomic imbalances, diseases and mortality. Parasympathetic activity and HRV have been associated with a wide range of conditions including CVD. Here we review the evidence linking HRV to established and emerging modifiable and non-modifiable CVD risk factors such as hypertension, obesity, family history and work stress. Substantial evidence exists to support the notion that decreased HRV precedes the development of a number of risk factors and that lowering risk profiles is associated with increased HRV. We close with a suggestion that a model of autonomic imbalance may provide a unifying framework within which to investigate the impact of risk factors, including psychosocial factors and work stress, on cardiovascular disease.